Terrorism and Migration: An Overview. Issue 2 (17th April 2022) - Helbling, Marc; Meierrieks, Daniel
Abstract: This article provides an overview of the literature on the relationship between terrorism and migration. It discusses whether and how (1) migration may be a cause of terrorism, (2) terrorism may influence natives' attitudes towards immigration and their electoral preferences and (3) terrorism may lead to more restrictive migration policies and how these in turn may serve as effective counter-terrorism tools. A review of the empirical literature on the migration–terrorism nexus indicates that (1) there is little evidence that more migration unconditionally leads to more terrorist activity, especially in Western countries, (2) terrorism has electoral and political (but sometimes short-lived) ramifications, for example, as terrorism promotes anti-immigrant resentment and (3) the effectiveness of stricter migration policies in deterring terrorism is rather limited, while terrorist attacks lead to more restrictive migration policies.